1987
DOI: 10.1007/bf01013237
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathy in agroecosystems: Wheat phytotoxicity and its possible roles in crop rotation

Abstract: The germination rates of cotton and wheat seeds were significantly affected by various extracts of wheat mulch and soils collected from the wheat field. This toxicity was even more pronounced against seedling growth. Five allelochemics: ferulic,p-coumaric,p-OH benzoic, syringic, and vanillic acids, were identified from the wheat mulch and its associated soil. Quantitatively, ferulic acid was found at higher concentrations thanp-coumaric acid in the soil. Various concentrations of ferulic andp-coumaric acids we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…There is also evidence of allelopathic properties of cereal residues in respect to inhibiting surface weed seed germination (Steinsiek et al 1982;Lodhi & Malik 1987;Jung et al 2004). Weeds will be controlled when the cover crop is cut, rolled flat or killed.…”
Section: Conservation Agriculture Definedmentioning
confidence: 99%
“…There is also evidence of allelopathic properties of cereal residues in respect to inhibiting surface weed seed germination (Steinsiek et al 1982;Lodhi & Malik 1987;Jung et al 2004). Weeds will be controlled when the cover crop is cut, rolled flat or killed.…”
Section: Conservation Agriculture Definedmentioning
confidence: 99%
“…Total water-soluble phenolics were determined as per Swain and Hillis (1959) using Folin-cicalteu reagent and are expressed as vanillic acid equivalents as it has been found as an allelochemical in wheat straw (Lodhi et al, 1987). The chemical characteristics of the extract are given in Table 1.…”
Section: Preparation Of Extractsmentioning
confidence: 99%
“…Indeed, there is an increasing interest in the weed suppressive ability of crops for both organic and conventional farming systems (Mason and Spaner 2006). Cereal crop plants, such as wheat (Lodhi et al 1987;Wu et al 2000a, b), barley (Overland 1966;Liu and Lovett 1993b;Fujii 2001) and rice (Olofsdotter et al 1999), have been shown to produce allelochemicals with a capacity to reduce growth of other plant species.…”
Section: Introductionmentioning
confidence: 99%